Monday

April 21, 2014

April 21, 2014

Posted by **Jessica** on Thursday, January 31, 2013 at 5:57pm.

3.4e^(2-2n)-9=-4 I don't know what is the step by step process. Help please!

- Logarithms (math) -
**Reiny**, Thursday, January 31, 2013 at 7:52pm3.4e^(2-2n)-9=-4

3.4e^(2-2n) = 5

e^(2-2n) = 5/3.4 = 50/34 = 25/17

e^(2-2n) = 25/17

ln both sides

ln( e^(2-2n) ) = ln (25/17)

(2-2n) lne = ln25 - ln17 , but lne = 1

2-2n = ln25-ln17

notice I have yet to touch a calculator ....

-2n = ln25 - ln17 - 2

n= (-1/2)ln25 + (1/2)ln17 + 1 , now to the calculator....

= appr .8072

**Related Questions**

algebra - So... I know the answer to the question because it's something we ...

math - question 1 use the laws of logarithms to simplify the expression Inx(x+2...

bobpursley, math,correction - Let n be a postive integer, then n+1 is the next ...

trigonometry - Use logarithms and the law of tangents to solve the triangle ABC...

Advanced Algebra - Solve the equation 4e^x -2=14 I got it this far... 4e^x=16 ...

Logarithms - solve 6 = 15^1-x by using logarithms. Round your asnwer to the ...

trigonometry - okay so i have this trigonometry problem were i HAVE to use ...

Abstract Algebra - If 2^n>n^2 and n>5, then 2^n+1>(n+1)^2 Proof: ...

kahyla - use the properties of logarithms to write the expression as a sum or ...

HELP. - Choose a formula for the nth term of the sequence: a2 , a4 , a6 , ... 2 ...